Introduction to Nanotheranostics - Tamil Selvan, Subramanian; Narayanan, Karthikeyan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book offers readers an introduction to the current status of nanoparticles and other nanomaterials that have potential applications in theranostics. Above all, it highlights the diagnostic and therapeutic applications of metallic (e.g. Au, Ag), semiconducting quantum dots (e.g. CdSe, CdTe), magnetic (e.g. Fe3O4, FePt, Co), and multifunctional (combination of two or three) nanoparticles. .
Nanoparticles in General -- Metallic Nanoparticles for Theranostics -- Semiconducting Nanoparticles or Quantum Dots for Theranostics -- Magnetic Nanoparticles for Theranostics.
Keywords: Biomedical engineering; Biomaterials; Medicine -- Research; Biology -- Research; Microtechnology; Microelectromechanical systems; Medical physics; Clinical biochemistry; Biomedical Engineering and Bioengineering; Biomaterials; Biomedical Research; Microsystems and MEMS; Medical Physics; Medical Biochemistry